The impact of mediated learning on the academic writing performance of medical students in flipped and traditional classrooms: scaffolding techniques - Laleh Khojasteh; Seyyed Ali Hosseini; Elham Nasiri (The Asia-Pacific Society for Computers in Education (APSCE), 2021)
Abstract Writing as a multiple-step process is one of the most complex and demanding skills for graduate students to master. Foreign or second language learners who are required to write for academic purposes at the university level may even find it more demanding to master. One of the ways of decreasing the burden of mastering this skill for learners is mediation, using scaffolding techniques to teach writing. Hence, having a good understanding of the impact(s) of adopting mediating or scaffolding techniques in writing classes is absolutely indispensable. To this end, the present study employed an experimental research design to investigate the impact of mediation in the flipped writing classrooms of the students of medicine. To peruse this goal, 47 medical students were selected through purposive sampling and put into control and treatment groups. Medical students in the treatment group watched teacher-made video content(s) before their writing classes. The students in this group experienced organized-interactive writing group activities in their classes. Unlike the experimental group, the students in the control group received all the instructions in the classroom and were assigned homework. The findings obtained through the ANOVA and t-test indicated that the students in the experimental group significantly outperformed their counterparts in the control group in terms of their writing. A probable conclusion could be that by requiring students to study in advance and take responsibility for their learning, flipped classroom can provide the opportunity for learners to actively construct knowledge rather than receive the information passively in the classroom. Flipped classroom can also cultivate interactive class time for teachers and enable them to invest in more fruitful academic practices, instead of asking students to spend a substantial amount of time each week doing homework independently.